The emergence and development of Arabic-Malay bilingual dictionaries in the Malay world: an analytical study - Dollah, Nafi @ Hanafi; Ahamad Shah, Mohamed Ismail; Abdullah, Nurazzelena (Universiti Sultan Azlan Shah ( USAS), 2016)
Abstract: This article aims at examining the emergence, development and contribution of the Arabic-Malay bilingual dictionaries in the Malay Archipelago. The paper hopes to promote Arabic and Malay as the languages of Islamic revealed knowledge. The process of Islamization of the Malay language has led to the borrowing of Arabic and Islamic words and also the transferring of knowledge of Islam into the Malay language. This study is significant as the investigation into the contributions of Arabic-Malay bilingual dictionaries to the Malay world has not been widely examined by scholars locally and internationally. In this respect, some studies have been conducted on selected dictionaries written in Malaysia in order to examine the extent to which the Malay translations meet the meaning given in its original language, which is Arabic, as well as its methodological aspects. Finally, some suggestions are also given on how to develop fully comprehensive Arabic-Malay bilingual dictionaries in the future.